MICROALBUMINURIA AS A FORECAST FACTOR FOR CARDIO-VASCULAR COMPLICATIONS AND A MARKER OF THERAPY EFFICACY IN PATIENTS WITH ARTERIAL HYPERTENSION - L. A. Haisheva; L. I. Katelnitskaya (Столичная издательская компания, 2016)
Aim. To assess the microalbuminuria (MAU) and vascular wall elasticity in patients with essential hypertension (HT) and evaluate the possibilities to reduce in fatal cardiovascular risk due to lisinopril (Listril, Dr Reddy's) therapy.Material and methods. 42 patients (60,3±0,83 y.o.) with HT were involved in the study. Pulse wave velocity was estimated by volume sphygmography. MAU levels were detected with micral-test (Roche Diagnostics, Germany). Patients received lisinopril as a first-step antihypertensive drug, if necessary the dose of lisinopril was increased or amlodipine was added. The treatment lasted for 12 weeks.Results. MAU was revealed more often in patients with increased body mass index as compared with whole population of hypertensive patients. MAU was associated with increased vascular wall stiffness. Lisinopril therapy during 4 weeks allowed to reach target level of blood pressure (BP) in 42,9% of patients and decreased in MAU level by 54,5%. Therapy continuation during 12 weeks allowed to reach target level of BP in 90,4% of patients and reduce in fatal cardiovascular risk by 36,6%.Conclusion. Lisinopril therapy resulted in significant reduction in BP, MAU and fatal cardiovascular risk in patients with HT.